Nursing Care for Patients with Suspect Dengue Fever at Private Hospital in Jakarta City - Diva Arta Carolina; Ernawati, Ernawati; Silalahi, Malianti; Noviantari, Komang (Jurnal MedScientiae, 2024)
Dengue fever is a disease caused by the dengue virus with symptoms: hyperthermia, joint pain, decreased platelets and leukocytes. However, these symptoms also often occur in viral infections in general, so proper assessment is needed in order to provide appropriate care. This case report is a nursing care for a patient with suspected dengue fever. Nursing care is provided by nursing students for 3 days at a private hospital in Jakarta with government health insurance facilities. Data collection was carried out by interviews, physical examination and diagnostic examination. The diagnosis was found: hyperthermia, acute pain, nausea, and risk of bleeding. In making plans, nurses make plans based on the patient's responses and symptoms. During treatment the leukocytes showed leukopenia which indicated a viral infection. Even though platelet values ​​decrease, they never fall below normal values. The nurse educates the patient not to brush his teeth to prevent gum bleeding. The patient was discharged on the third day of treatment with normal platelet values. Platelet values, which are always within normal limits during the treatment period, cannot confirm that the patient has dengue fever. Nursing care is provided based on the response and symptoms that arise in the patient. Regardless of whether the medical diagnosis confirmed is dengue fever, the nursing process is carried out based on the response or symptoms that appear in the patient.